2012
DOI: 10.1186/1478-811x-10-34
|View full text |Cite
|
Sign up to set email alerts
|

FGF-9 accelerates epithelial invagination for ectodermal organogenesis in real time bioengineered organ manipulation

Abstract: BackgroundEpithelial invagination is important for initiation of ectodermal organogenesis. Although many factors regulate ectodermal organogenesis, there is not any report about their functions in real-time study. Electric cell-substrate impedance sensing (ECIS), a non-invasive, real-time surveillance system, had been used to detect changes in organ cell layer thickness through quantitative monitoring of the impedance of a cell-to-microelectrode interface over time. It was shown to be a good method for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…FGF9 is secreted by both mesothelial and epithelial cells, and only is expressed in the epithelium. It is involved in the early differentiation of epithelial cell layers, in epithelial invagination and ectodermal organogenesis (ectodermal organs include hair, feathers, scales, teeth, beaks, nails, horns and several eccrine glands) [ 27 , 30 ]. In hair follicles, FGF9 mRNA expression is highest in telogen, at 22 days after depilation, at approximately 300 mRNA copy numbers per cell; FGFR2 and FGFR3 are abundantly expressed in anagen VI (at 18 days), at approximately 10,000 and 28,000 mRNA copy numbers per cell respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF9 is secreted by both mesothelial and epithelial cells, and only is expressed in the epithelium. It is involved in the early differentiation of epithelial cell layers, in epithelial invagination and ectodermal organogenesis (ectodermal organs include hair, feathers, scales, teeth, beaks, nails, horns and several eccrine glands) [ 27 , 30 ]. In hair follicles, FGF9 mRNA expression is highest in telogen, at 22 days after depilation, at approximately 300 mRNA copy numbers per cell; FGFR2 and FGFR3 are abundantly expressed in anagen VI (at 18 days), at approximately 10,000 and 28,000 mRNA copy numbers per cell respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation and function of the dental mesenchyme are regulated by Lhx8 via WNT and TGFβ pathways [23]. FGF9 is also involved in epithelial invagination and initiation of ectodermal organogenesis [24].…”
Section: Fgfsmentioning
confidence: 99%
“…[20] Rhodamine B [53,54] was chosen as the model system to demonstrate high photodegradation efficiency because of its high stability under visible light irradiation and reduced biodegradability. [55] This is especially important in the context of heterogenous photocatalysis being widely used for wastewater treatment, with previous studies being based on either traditional Ti [56] or ZnO [57] catalysts, tantalates [58] or germanates. [59] Further, the focus on rhodamine B is also supported by previous studies that showed that the dye is an active carcinogen, [60] more difficult to remove than other dyes such as methyl orange or methylene blue.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%